GL2-type homeobox gene Roc4 in rice promotes flowering time preferentially under long days by repressing Ghd7. (November 2016) - Wei, Jinhuan; Choi, Heebak; Jin, Ping; Wu, Yunfei; Yoon, Jinmi; Lee, Yang-Seok; Quan, Taiyong; An, Gynheung
Highlights: Overexpression of Roc4 causes early flowering preferentially under long-day conditions. Roc4 promotes flowering time by repressing Ghd7 . Phytochromes and OsGI function upstream of Roc4 . Roc4 : GUS transgenic plants showed Roc4 ubiquitously expressed in leaves and roots. Roc4 has transcriptional activation activity in the N-terminal region of the START domain. Abstract: Under long day (LD) lengths, flowering can be delayed in rice by modulating several regulatory genes. We found activation tagging lines that showed an early flowering phenotype preferentially under LD conditions. Expression of Rice outermost cell-specific gene 4 ( Roc4 ), encoding a homeodomain Leu-zipper class IV family protein, was significantly increased. Transcript levels of Grain number, plant height, and heading date7 ( Ghd7 ) were significantly reduced while those of Ghd7 downstream genes were increased. However, other flowering regulators were unaffected. Whereas constitutive overexpression of Roc4 in 'Dongjin' japonica rice, which carries active Ghd7, also caused LD-preferential early flowering, its overexpression in 'Longjing27′ rice, which is defective in functional Ghd7, did not produce the same result. This confirmed that Roc4 regulates flowering time mainly through Ghd7 . Phytochromes and O. sativa GIGANTEA ( OsGI ) function upstream of Roc4 . Transgenic plants showed ubiquitous expression of the β -glucuronidase reporter gene under the Roc4 promoter. Furthermore, Roc4 had transcriptional activation activity in the N-terminal region of the StAR-related lipid-transfer domain. All of these findings are evidence that Roc4 is an LD-preferential flowering enhancer that functions downstream of phytochromes and OsGI, but upstream of Ghd7 .